Effectiveness of cyclosporine as a treatment for steroid-resistant Cronkhite-Canada syndrome; two case reports. Issue 1 (December 2016) - Yamakawa, Kohei; Yoshino, Takuya; Watanabe, Kotaro; Kawano, Koichiro; Kurita, Akira; Matsuzaki, Naomi; Yuba, Yoshiaki; Yazumi, Shujiro
Abstract Background Cronkhite-Canada syndrome (CCS) is a rare non-inherited disorder, characterized by gastrointestinal polyposis and ectodermal changes. The pathophysiology remains unclear. Treatment with corticosteroids is considered the mainstay treatment because of its high efficacy. However, some patients have steroid-resistant CCS. The therapeutic strategy for steroid-resistant CCS is not yet established. We report two cases with steroid-resistant CCS that were effectively treated with cyclosporine (CyA). We evaluated the therapeutic strategy for steroid-resistant CCS based on reviews of previous reports. Case presentation Our patients with CCS were first treated with prednisolone. No clinical response was noted, and treatment with CyA was initiated. After beginning CyA treatment, both clinical symptoms and polyposis markedly improved. Up to the present, 55 cases of CCS treated with corticosteroids and their response were reported. Out of the 57 patients, including our 2 cases, 9 (16 %) did not respond clinically to corticosteroids. In 7 of the 9 steroid-resistant cases, the prognosis after corticosteroids treatment was described. In 5 of the 7 steroid-resistant cases, immunosuppressive treatments induced remission. In 4 of these 5 cases, moreover, the key drug of treatments was calcineurin inhibitor. Conclusions Treatment with calcineurin inhibitor, such as CyA, could be a potential option for steroid-resistant CCS.